The gendered impacts of agricultural asset transfer projects: Lessons from the Manica smallholder dairy development program - Johnson, Nancy L.; Njuki, Jemimah; Waithanji, Elizabeth M.; Nhambeto, M.; Rogers, M.; Kruger, E.H. (Informa UK Limited, 2015)
This article explores the gendered impacts of a development project that provided dairy training and a superior breed of cattle to households as part of a broader effort to develop a smallholder-friendly, market-oriented dairy value chain in the Manica province of Mozambique. The project first targeted households, registered cows in the names of the household heads, and, initially, trained these cow owners in various aspects of dairy production and marketing. Subsequently, the training was expanded to two members per household to increase the capacity within households to care for cows, a change that resulted in the training of a significant number of women. Using qualitative and quantitative data on dairy production and consumption, and on gendered control over income and assets, the article explores how men and women participated in and benefited from the Manica Smallholder Dairy Development Program (MSDDP). We found that despite being registered in the name of men, in practice, dairy cattle are in some cases viewed as jointly owned by both men and women. Beneficiary households dramatically increased dairy production and income, with men, women, and children all contributing labor to this endeavor. Women’s incentives for participation in dairy were less clear. Despite their recognized rights and responsibilities related to dairy cow management, women exercised relatively little control over milk and milk income as compared to men. This article explores the various monetary and nonmonetary benefits of MSDDP and dairying for women along with their implications for the level of effort put in by women, and the overall project outcomes.